2012
DOI: 10.1504/eg.2012.048005
|View full text |Cite
|
Sign up to set email alerts
|

Citizens' perceptions of corruption and e-governance in Jordan, Ethiopia and Fiji - the need for a marketing approach

Abstract: The purpose of this research is to assess citizen's perceptions of corruption and e-governance in Jordan, Ethiopia, and Fiji. The research is based on surveys using structured questionnaires and focus group interviews. Conclusions are derived from a mix of descriptive and inferential analysis. The survey covers a total of 1212 respondents using stratified sampling. Findings reveal that public sector corruption and demands for bribes are increasing in each country. Only a few people are aware of e-governance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Like much of the other literature reviewed, however, Moraa and her colleagues did not provide evidence that these technologies were having an impact on service delivery. E-governance (using ICTs to improve governance outcomes), e-government (increasing efficiency of government services through creation of publicly accessible online platforms), and mobile governance (m-governance) were also major themes in the literature (Atnafu et al 2011;Crandall and Mutuku 2011;Minishi-Majanja and Ondari-Okemwa 2009;Mitullah and Waema 2011;Mutula 2008;Pathak et al 2007;Pathak et al 2012;Rorissa and Demissie 2010;Singh et al 2010;Thomas et al 2010;Waema 2011;Yonazi et al 2012). Many of the pieces in this category, however, focused on measuring the e-readiness of towns and/or countries rather than evaluating the results of e-governance initiatives.…”
Section: Icts and Statebuildingmentioning
confidence: 99%
See 2 more Smart Citations
“…Like much of the other literature reviewed, however, Moraa and her colleagues did not provide evidence that these technologies were having an impact on service delivery. E-governance (using ICTs to improve governance outcomes), e-government (increasing efficiency of government services through creation of publicly accessible online platforms), and mobile governance (m-governance) were also major themes in the literature (Atnafu et al 2011;Crandall and Mutuku 2011;Minishi-Majanja and Ondari-Okemwa 2009;Mitullah and Waema 2011;Mutula 2008;Pathak et al 2007;Pathak et al 2012;Rorissa and Demissie 2010;Singh et al 2010;Thomas et al 2010;Waema 2011;Yonazi et al 2012). Many of the pieces in this category, however, focused on measuring the e-readiness of towns and/or countries rather than evaluating the results of e-governance initiatives.…”
Section: Icts and Statebuildingmentioning
confidence: 99%
“…A handful of the e-governance studies (Atnafu et al, 2011;Crandall and Mutuku 2011;Mitulla and Waema 2011;Ochara 2012;Pathak et al 2007Pathak et al , 2012Singh et al 2010;Thomas et al 2010;Waema 2011;Yonazi et al 2012) attempted to assess the impact of e-government projects through interviews with citizens about how they themselves assess these initiatives. Crandall and Mutuku (2011) noted that health, education, and immigration services are among the top sectors employing e-services in Kenya, but found that most of the individuals surveyed believed face-to-face interaction with government is most effective.…”
Section: Icts and Statebuildingmentioning
confidence: 99%
See 1 more Smart Citation
“…After extensive searching, we could find a total of ten articles only. A study by Pathak et al (2012) found that the main challenges for e-government development in Fiji were the establishment of integrated information systems through interdepartmental coordination, and achieving efficiency and effectiveness of e-services. The survey of Singh et al (2010) found that Fiji lacked the regulations and institutions to ensure the security of e-government services.…”
Section: Researchmentioning
confidence: 99%
“…Second, the prior research tended to deal with different perspectives on Fiji e-government in an incoherent fashion. For example, three of the ten articles (Pathak et al 2009(Pathak et al , 2012Singh et al 2010) investigated the possible effect of e-government on corruption, two on service delivery, and two on government websites. Most of the studies were conducted from the supply (government) perspective.…”
Section: Researchmentioning
confidence: 99%